2013
DOI: 10.1016/j.humpath.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest transcription factor Sox10 is preferentially expressed in triple-negative and metaplastic breast carcinomas

Abstract: Summary The transcription factor Sox10 mediates the differentiation of neural crest–derived cells, and Sox10 labeling by immunohistochemistry (IHC) is used clinically primarily to support the diagnosis of melanoma. Sox10 expression by IHC has been previously documented in benign breast myoepithelial cells but not in breast carcinomas. Here, we report the first systematic study of Sox10 expression in invasive ductal carcinomas subclassified by IHC-defined molecular subtype (100 cases), as well as in 24 cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
133
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(162 citation statements)
references
References 30 publications
12
133
3
Order By: Relevance
“…activate an endogenous autoregulatory network in adult stem cells and reconstitute an entire mammary gland (Guo et al 2012). Meanwhile, showing stem cell characteristics such as self-renewal and multi-potency, Sox10 is one of the most studied Sox family genes, mainly because of their role in the survival of neural crest cells and compilation into neural-crest-derived melanocytes and glia (Cimino-Mathews et al 2013;Ivanov et al 2013). Invasive breast carcinomas, especially those with triple negative hormone expression and metastases seem to be supportive for myoepithelial differentiation (CiminoMathews et al 2013;Ivanov et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…activate an endogenous autoregulatory network in adult stem cells and reconstitute an entire mammary gland (Guo et al 2012). Meanwhile, showing stem cell characteristics such as self-renewal and multi-potency, Sox10 is one of the most studied Sox family genes, mainly because of their role in the survival of neural crest cells and compilation into neural-crest-derived melanocytes and glia (Cimino-Mathews et al 2013;Ivanov et al 2013). Invasive breast carcinomas, especially those with triple negative hormone expression and metastases seem to be supportive for myoepithelial differentiation (CiminoMathews et al 2013;Ivanov et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sox9, Sox10 and Slug were shown to be associated with poor overall survival in breast cancer (Cimino-Mathews et al 2013;Guo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,24 Reactivity for SOX10 is also observed in astrocytomas, myoepithelial tumors, selected other types of salivary gland neoplasms, and a subset of breast carcinomas, particularly basal-like, 'triple-negative, ' and metaplastic carcinomas. 21,25,26 The most recent addition to this group of markers is SATB2 (special AT-rich sequence-binding protein 2).…”
Section: Lineage-restricted Transcription Factorsmentioning
confidence: 99%
“…18,19 Previous studies have shown that the expression of this nuclear transcription factor, detected by immunohistochemistry, is sensitive for a variety of Schwannian and melanocytic neoplasms, [20][21][22] benign myoepithelial cells and rarely other tumor types. 23 However, data specifically comparing genetically confirmed synovial sarcoma, including intraneural synovial sarcoma, with malignant peripheral nerve sheath tumor with respect to SOX10 expression is limited. In the present study, we evaluate the utility of SOX10 immunohistochemistry in differentiating malignant peripheral nerve sheath tumor from synovial sarcoma.…”
mentioning
confidence: 99%